Odpowiedzi

Najlepsza Odpowiedź!
2010-01-23T17:07:41+01:00
4.
a) 5x^2-15x = x(5x-15)
b) 3by-6b = 3b(y-2)
c) -8xy+8x = 8x(-y+1)
d) 10a^2-2ab = 2a(5a-b)
e) xy-x^2y = xy(1-x)
f) 6a-24b+30c = 6(a-4b+5c)
g) 12ab^2+16b^2 = 4b(3ab+4b)
h) x^3-2x^2+x = x(x^2-2x+1)
i) 2xy+3x-x^2y = x(2y+3-xy)

5.
a) 3x+12/3 = 3(x+4)/3 = x+4
b) 8y-4/4 = 4(2y-2)/4 = 2y-2
c) -10a+15/5 + 12a-18/6 = 5(-2a+3)/5 + 6(2a-3)/6 = -2a+3 + 2a-3 = 0
d) 14x-21/7 - 64-16x/8 = 7(2x-3)/7 - [16(-x+4)/8] = 2x-3 -[2(-x+4)] = 2x-3 +2x -8 = 4x - 11

6.
a) 28*17 - 28*15 = 28(17-15) = 28*2 = 56
b) 31*15 -62*7 = 31*15 - 31*2*7 = 31*15 -31*14 = 31*1 = 31
c) 13*49 - 26*27 = 13*49 - 13*2*27 = 13*49 - 13^54 = 13*(-5) = -65